Реалізація права на працю за строковим трудовим договором - Якушев, І.; Yakushev, I. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Стаття присвячена аналізу підстав укладення та припинення строкових трудових договорів. Розкрито особливості правового регулювання необхідності та можливості укладення строкового трудового договору. Розглянуто вплив юридичного та фактичного становища працівника і роботодавця на визначення строку трудового договору. The article is devoted to the analysis of the grounds for concluding and termination of the fixed-term employment contracts. The study has revealed that a fixed-term employment contract is concluded in the cases that are caused by the objective circumstances (the character and conditions of the future work do not allow to conclude an employment contract for an indefinite period), and in cases of subjective nature, when the term of the employment contract is agreed by the parties and depends on their will (interests of the employee or cases provided by legislative acts). The position of the Supreme Court of Ukraine is defined as untenable, since it equals the concepts of «interest» and «desire» of the employee, since a fixed-term employment contract may involve a number of disadvantages for the employee. In this regard, the scope of the necessary and possible situations for concluding a fixed-term employment contract have been determined. To ensure labor rights of the employee at the legislative level the author suggests to specify in the contract the length of time the employee agrees to work for the company, e.i to determine clearly the duration of a fixed-term employment contract. The emphasis is laid on the necessity to bring national legislation in line with the requirements of the international norms which specify that labor relations with employees shall not be terminated unless there are legal grounds for such termination related to the abilities or behavior of an employee or it is caused by current HR employment opportunities of the company.
On the Issue of the Medical Services Contract Provision
Keywords: право на працю; трудовий договір; строк трудового договору; види строкових трудових договорів; the right to work; the employment contract; the term of the employment contract; types of fixed-term employment contracts